Enough? The role of sufficiency in European energy and climate plans. (October 2021) - Zell-Ziegler, Carina; Thema, Johannes; Best, Benjamin; Wiese, Frauke; Lage, Jonas; Schmidt, Annika; Toulouse, Edouard; Stagl, Sigrid
Abstract: Energy sufficiency is one of the three energy sustainability strategies, next to energy efficiency and renewable energies. We analyse to what extent European governments follow this strategy, by conducting a systematic document analysis of all available European National Energy and Climate Plans (NECPs) and Long-Term Strategies (LTSs). We collect and categorise a total of 230 sufficiency-related policy measures, finding large differences between countries. We find most sufficiency policies in the transport sector, when classifying also modal shift policies to change the service quality of transport as sufficiency policies. Types of sufficiency policy instruments vary considerably from sector to sector, for instance the focus on financial incentives and fiscal instruments in the mobility sector, information in the building sector, and financial incentive/tax instruments in cross-sectoral application. Regulatory instruments currently play a minor role for sufficiency policy in the national energy and climate plans of EU member states. Similar to energy efficiency in recent decades, sufficiency still largely referred to as micro-level individual behaviour change or necessary exogenous trends that will need to take place. It is not treated yet as a genuine field of policy action to provide the necessary framework for enabling societal change. Highlights: Assessment of sufficiency in National Energy and Climate Plans and Long-Term Strategies. Sufficiency-related measures exist in many NECPs/LTSs, predominantly in the transport sector. Sufficiency is underrepresented compared to efficiency and renewables. Regulatory instruments to reduce energy demand are rare, fiscal/economic instruments dominate. The template for EU NECPs and LTSs lacks a sufficiency chapter.